2015
DOI: 10.1161/circulationaha.114.013003
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Signal Transducer and Activator of Transcription-3 Promotes Angiogenesis and Neuroplasticity Long-Term After Stroke

Abstract: Background-Poststroke angiogenesis contributes to long-term recovery after stroke. Signal transducer and activator of transcription-3 (Stat3) is a key regulator for various inflammatory signals and angiogenesis. It was the aim of this study to determine its function in poststroke outcome. Methods and Results-We generated a tamoxifen-inducible and endothelial-specific Stat3 knockout mouse model by crossbreeding Stat3 floxed/KO and Tie2-Cre ERT2 mice. Cerebral ischemia was induced by 30 minutes of middle cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 35 publications
(38 reference statements)
2
65
0
Order By: Relevance
“…The JAK2/STAT3 signaling pathway is involved in cell proliferation, cell-cycle progression, and angiogenesis, and it is associated with antiphospholipid antibodies-mediated inhibition of endometrial angiogenesis and leptin-induced neovascularization in diabetic retinopathy (Darnell et al 1994;Suganami et al 2004;D'Ippolito et al 2012;Raible et al 2014). Especially, increasing evidence has shown that the JAK2/STAT3 signaling pathway plays a primary role in stroke induced angiogenesis (Sakata et al 2012;Hoffmann et al 2015). Thus, we investigated the role of the JAK2/ STAT3 signaling pathway in Sals-induced post-stroke angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The JAK2/STAT3 signaling pathway is involved in cell proliferation, cell-cycle progression, and angiogenesis, and it is associated with antiphospholipid antibodies-mediated inhibition of endometrial angiogenesis and leptin-induced neovascularization in diabetic retinopathy (Darnell et al 1994;Suganami et al 2004;D'Ippolito et al 2012;Raible et al 2014). Especially, increasing evidence has shown that the JAK2/STAT3 signaling pathway plays a primary role in stroke induced angiogenesis (Sakata et al 2012;Hoffmann et al 2015). Thus, we investigated the role of the JAK2/ STAT3 signaling pathway in Sals-induced post-stroke angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…; Hoffmann et al . ). However, an outstanding question is that angiogenic vessels are permeable, so that maturation of the vessel walls is necessary to ensure a stable vascular system, and the coverage of endothelium by pericytes and astrocytic endfeet delivers (at least partly) the solution (Rigau et al .…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, it was reported that the activation of the JAK/STAT3 pathway promotes synapse formation and axon outgrowth in the injured brain (Hoffmann et al . ; Chen et al . ).…”
Section: Discussionmentioning
confidence: 99%